2019
DOI: 10.1177/1558944719884655
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of a Non-Invasive Shot Blocking Device for Reducing Pain of In-office Injections in Hand Surgery

Abstract: Background: The gate control theory asserts that non-painful stimuli can block pain perception. The ShotBlocker™ device is a plastic disk with blunt projections that rests on the skin, and we hypothesize that it will reduce pain during hand injections. Methods: This is a prospective randomized trial of 117 patients undergoing injections for common hand conditions. Patients were randomized into 3 groups: device, placebo (device with projections removed), and control. Patients recorded on an analog pain scale th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…Current physical products for pain relief, such as ShotBlocker®, based on the gate control theory described by Melzack and Wall [ 19 ], have blunt projections to stimulate larger afferent nerve fibers when compressing around the injection site, thus inhibiting pain perception by exerting an inhibitory effect on afferent sensory fibers by activating cells within the substantia gelatinosa in the dorsal horn of the spinal cord. Applying ShotBlocker® for local anesthesia in general places has proven effective for pain relief [ 4 , 5 ]. A recent meta-analysis concluded that the application of ShotBlocker® can reduce IM injection pain in adults [ 20 ], although two additional randomized controlled trials in IM injection and spinal anesthesia reported contradicting results [ 13 , 21 ] These different study results may be affected by heterogeneity of the injection site, volume, and depth [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Current physical products for pain relief, such as ShotBlocker®, based on the gate control theory described by Melzack and Wall [ 19 ], have blunt projections to stimulate larger afferent nerve fibers when compressing around the injection site, thus inhibiting pain perception by exerting an inhibitory effect on afferent sensory fibers by activating cells within the substantia gelatinosa in the dorsal horn of the spinal cord. Applying ShotBlocker® for local anesthesia in general places has proven effective for pain relief [ 4 , 5 ]. A recent meta-analysis concluded that the application of ShotBlocker® can reduce IM injection pain in adults [ 20 ], although two additional randomized controlled trials in IM injection and spinal anesthesia reported contradicting results [ 13 , 21 ] These different study results may be affected by heterogeneity of the injection site, volume, and depth [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this application, the IM injection site is compressed using a blunt-tipped plastic disk with many projections. Although this method may relieve injection pain intensity [ 2 5 ], several studies have contradicting conclusions. Most randomized controlled trials have focused on its application in deep site injection (i.e., IM, spinal, and joint anesthesia).…”
Section: Introductionmentioning
confidence: 99%